The Difunta Correa Metasedimentary Sequence (NW Argentina): relict of a Neoproterozoic platform? elemental and Sr-Nd isotope evidence - Ramacciotti, Carlos Dino (2015)
The Sierra de Pie de Palo (Western Sierras Pampeanas, Argentina)in the Andean foreland is mainly formed by a Mesoproterozoic basementand an Ediacaran metasedimentary cover referred to as theDifunta Correa metasedimentary sequence. The latter is key to understandingthe characteristics of this region prior to the early Cambrianassembly of SW Gondwana. It is composed of low- to medium grademetamorphic rocks (metasandstones, mica-schists, Ca-pelitic schists,metaconglomerates, marbles and less abundant amphibolites) that canbe grouped into four informal lithostratigraphic units. The chemicalcomposition of these rocks allows to classify the siliciclastic protolithsas shales, Fe-shales and immature sandstones (wackes, sub-litharenites,litharenites and Fe-sandstones). The sediments were derived from anevolved felsic to intermediate continental source and were depositedon a continental passive margin overlaying a Mesoproterozoic basementthat crops out at several places of the Western Sierras Pampeanas.Thick marine carbonate beds with seawater isotope composition,phosphatic clasts and the lack of contemporaneous, arc related igneousrocks, also support a passive margin sedimentation. Phosphaticclasts within metaconglomerates are described for the first time inthe Sierras Pampeanas and were probably formed after an importantNeoproterozoic glaciation (Marinoan). We further suggest, based onour data and previous works, that the passive margin probably belongedto the Paleoproterozoic MARA (acronym of Maz, Arequipa, Río Apa)continental block. MARA, which remained juxtaposed to Laurentiasince the middle to late Mesoproterozoic orogenies until its eventualdrifting in the late Neoproterozoic, finally accreted to SW Gondwanain early Cambrian times during the Pampean orogeny.